Draft genome sequence data of Cercospora kikuchii, a causal agent of Cercospora leaf blight and purple seed stain of soybeans - Sautua, Francisco José; Gonzalez, Sergio Alberto; Doyle, Vinson P.; Berretta, Marcelo Facundo; Gordó, Manuela; Scandiani, María Mercedes; Rivarola, Maximo Lisandro; Fernandez, Paula Del Carmen; Carmona, Marcelo Anibal (Elsevier, 2020)
Cercospora kikuchii (Tak. Matsumoto & Tomoy.) M.W. Gardner 1927 is an ascomycete fungal pathogen that causes Cercospora leaf blight and purple seed stain on soybean. Here, we report the first draft genome sequence and assembly of this pathogen. The C. kikuchii strain ARG_18_001 was isolated from soybean purple seed collected from San Pedro, Buenos Aires, Argentina, during the 2018 harvest. The genome was sequenced using a 2 × 150 bp paired-end method by Illumina NovaSeq 6000. The C. kikuchii protein-coding genes were predicted using FunGAP (Fungal Genome Annotation Pipeline). The draft genome assembly was 33.1 Mb in size with a GC-content of 53%. The gene prediction resulted in 14,856 gene models/14,721 protein coding genes. Genomic data of C. kikuchii presented here will be a useful resource for future studies of this pathosystem. The data can be accessed at GenBank under the accession number VTAY00000000 https://www.ncbi.nlm.nih.gov/nuccore/VTAY00000000.